Methodology for Fault Detection Applied in Photovoltaic Plants Based on Inverter Power Curve Analysis - Paulo A. V. Vieira; João M. S. Callegari; Heverton Augusto Pereira (Eletrônica de Potência)
The maintenance of photovoltaic plants is crucial to ensure their proper performance, longevity, and efficiency, while also enhancing the return on investment and contributing to sustainable energy production. In such context, this paper proposes a methodology to characterize the main issues in photovoltaic plants, based on the analysis of the proposed inverter output power curve. Through power curve analysis, the most common anomalies and faults encountered in inverters are identified, providing a valuable tool for the early detection of operational issues. Additionally, power curve analysis allows a comparison between projected and actual values of generated energy, offering an index of system energy losses. Lastly, an economic analysis is presented, ranking inverters based on the magnitude of their energy losses, from highest to lowest. This analysis provides important insights for prioritizing maintenance actions and allocating resources to enhance generation returns.